PERKAWINAN WANITA HAMIL KARENA ZINA DALAM PASAL 53 KOMPILASI HUKUM ISLAM PERSPEKTIF MAQASID AL SHARI’AH IMAM AL SHATIBI - Albar Firdaus (Indonesian Journal of Islamic Law, 2019)
The phenomenon of free social interaction in society has generated various negative impacts, particularly among Muslim communities in Indonesia, one of which is the practice of adultery resulting in pregnancy outside of marriage. In the Indonesian legal context, the issue of marriage involving pregnant women due to adultery is specifically regulated in Article 53 of the Compilation of Islamic Law (Kompilasi Hukum Islam/KHI), which permits a woman who becomes pregnant out of wedlock to marry the man responsible for the pregnancy. This provision has generated significant controversy, as it contains both potential benefits and harms from social, moral, and legal perspectives. Therefore, this study examines the regulation through the framework of maqāṣid al-sharī‘ah, particularly as formulated by Imam al-Shāṭibī, which emphasizes that the ultimate objective of Islamic law is to realize public welfare (maṣlaḥah) and prevent harm (mafsadah) in human life.